Synthesis of Paraffin-Based Phase Change Material (PCM) Composites with Expanded Graphite as a Cooling System for Solar Panels - Azka, Muhamad Fauzan; Hidayat, Sahrul; Gultom, Noto Susanto; Setianto, Setianto; Nurhilal, Otong (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
The increase in the surface temperature of solar panels can reduce their efficiency. This issue can be mitigated through the implementation of cooling systems. One of the currently developed cooling methods involves the use of phase change materials (PCMs). Paraffin is the most commonly used PCM for solar panel cooling systems due to its melting point, which falls within the operating temperature range of solar panels. However, paraffin has a drawback in the form of low thermal conductivity. To overcome this limitation, paraffin is often composited with materials possessing high thermal conductivity, such as graphite. Graphite can also be expanded to alter its mechanical and thermal properties. The expansion of graphite using a solution of H₂SO₄ and K₂S₂O₈ can increase its surface area to 15.669 m²/g and 201.945 m²/g for 5% and 10% solid–liquid variation ratios, respectively. The addition of expanded graphite (EG) can also enhance the thermal conductivity of the PCM to 0.31 W/mK, 0.37 W/mK, and 0.44 W/mK with 5 wt%, 10 wt%, and 15 wt% EG additions, respectively. The paraffin-based PCM cooling system can reduce the average surface temperature by 15.36% and increase the overall efficiency by 0.3%. A PCM cooling system composed of paraffin and expanded graphite (95%/5%) can lower the average surface temperature by 20.32% and increase total efficiency by 0.4%. The PCM system with a 90%/10% paraffin-EG composition can reduce the surface temperature by 32.44% and enhance total efficiency by 1.2%. Meanwhile, the 85%/15% paraffin-EG cooling system achieves a temperature reduction of 32.52% and a total efficiency improvement of 1.27% compared to the system without cooling.